Deep vein thrombosis, an unreported first manifestation of polyglandular autoimmune syndrome type III. (28th July 2016) - Horsey, M; Hogan, P; Oliver, T
Summary: A 71-year-old woman with severe right lower leg pain, edema and erythema was presented to the Emergency Department and was found to have an extensive deep vein thrombosis (DVT) confirmed by ultrasound. She underwent an extensive evaluation due to her prior history of malignancy and new hypercoagulable state, but no evidence of recurrent disease was detected. Further investigation revealed pernicious anemia (PA), confirmed by the presence of a macrocytic anemia (MCV=115.8fL/red cell, Hgb=9.0g/dL), decreased serum B12 levels (56pg/mL), with resultant increased methylmalonic acid (5303nmol/L) and hyperhomocysteinemia (131μmol/L), the presumed etiology of the DVT. The patient also suffered from autoimmune thyroid disease (AITD), and both antithyroglobulin and anti-intrinsic factor antibodies were detected. She responded briskly to anticoagulation with heparin and coumadin and treatment of PA with intramuscular vitamin B12 injections. Our case suggests that a DVT secondary to hyperhomocystenemia may represent the first sign of polyglandular autoimmune syndrome III-B (PAS III-B), defined as the coexistent autoimmune conditions AITD and PA. It is important to recognize this clinical entity, as patients may not only require acute treatment with vitamin B12 supplementation and prolonged anticoagulation, as in this patient, but may also harbor other autoimmune diseases. Learning points: A DVT can be the first physical manifestation of a polyglandular autoimmune syndrome. Hyperhomocysteinemia secondary to pernicious anemia should be considered as an etiology of an unprovoked DVT in a euthyroid patient with autoimmune thyroid disease. Patients with DVT secondary to hyperhomocysteinemia should undergo screening for the presence of co-existent autoimmune diseases in addition to treatment with B12 supplementation and anticoagulation to prevent recurrent thromboembolism.